Movement of Chlorinated Solvents and Other Volatile Organics Through Plants Monitored by Fourier Transform Infrared (FT-IR) Spectrometry - L. C. Davis; S. Vanderhoof; J. Dana; K. Selk; K. Smith; B. Goplen; L. E. Erickson (Journal of Hazardous Substance Research, 1998)
Plants have a large capacity to transfer water from soil to the atmosphere. Soluble contaminants may be carried with that water, with a relative extent of transfer that depends on their octanol-water or organic matter-water partition coefficient. We measured the transfer rate for several solvents that vary in volatility and solubility, including trichloro ethylene, trichloroethane, chloroform, dichloromethane, diethyl ether, and methyl-t-butyl ether. We tested them alone and in several combinations. An extractive Fourier Transform Infrared (FT-IR) Spectrometer (Gasmet, produced by Temet Instruments) was used to measure concentrations in the gas phase above plants which had their root system immersed in water containing the contaminant. Deuterated water was used to trace transpiration rate. Hybrid poplars (Populus deltoides x nigra) and saltcedar (Tamarix parviflora) gave similar results, indicating relatively free movement of the indicated solvents, alone or in combinations. Alfalfa (Medicago sativa) also permitted transfer of those compounds that were tested.
Keywords: volatile contaminants; FT-IR; plants; transpiration; phytoremediation